The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1111/j.1476-5381.1993.tb13530.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of muscarinic receptors in murine airways

Abstract: 1 The effects of muscarinic receptor antagonists considered to be selective for Ml receptors (pirenzepine; PZ), M2 receptors (AFDX-1 16), and for M3 receptors (4-diphenyl acetoxy N-methylpiperidine (4-DAMP)) were used to investigate the existence of muscarinic receptor subtypes in murine airways. Atropine was used as a nonselective antagonist. The effects of these antagonists were studied upon tracheal contractions induced either by EFS (electric field stimulation) or by application of an exogenous cholinocept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
17
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 37 publications
8
17
0
Order By: Relevance
“…In our study AF-DX 116 had at least a 100 fold lower affinity than 4-DAMP for muscarinic receptors in CM (7.36) and LM (6.44). The pA2 value in LM is similar to the low affinity of AF-DX 116 for the muscarinic receptor subtype in the guineapig ileum (Giachetti et al, 1986) but the higher value for CM is more similar to that observed in guinea-pig atrium (Giachetti et al, 1986). It is unclear at this time why there is a difference for AF-DX 116 between the CM and LM muscle coats as this was not observed with the other muscarinic antagonists.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In our study AF-DX 116 had at least a 100 fold lower affinity than 4-DAMP for muscarinic receptors in CM (7.36) and LM (6.44). The pA2 value in LM is similar to the low affinity of AF-DX 116 for the muscarinic receptor subtype in the guineapig ileum (Giachetti et al, 1986) but the higher value for CM is more similar to that observed in guinea-pig atrium (Giachetti et al, 1986). It is unclear at this time why there is a difference for AF-DX 116 between the CM and LM muscle coats as this was not observed with the other muscarinic antagonists.…”
Section: Discussionmentioning
confidence: 56%
“…AF-DX 116 has an affinity proffile of M2 > M 1> M4 > M3 in functional pharmacological studies (Hammer et al, 1986;Giachetti et al, 1986;Giraldo et al, 1987) and a similar profile in human cloned muscarinic receptors (Dorje et al, 1991). In our study AF-DX 116 had at least a 100 fold lower affinity than 4-DAMP for muscarinic receptors in CM (7.36) and LM (6.44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that the response via M 3 muscarinic receptors and the number of M 3 muscarinic receptors might be greater in BHS than in BHR. After treatment with 4-DAMP (10 -5 M), no contraction was observed in either BHS or BHR, because it nonselectively blocked muscarinic receptors [8,11] and inhibited CCh-induced smooth muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, also in other species, including humans, the comparison of the pre-and postjunctional potencies of the M1-, M2-and M3-selective antagonists has suggested that autoinhibition of acetylcholine release is mediated via an 'M2-like' receptors (22)(23)(24)(25). In any case, even thought the muscarinic autoreceptors may be a different receptor subtype to the classical M2, the results that we obtained with pilocarpine and methoctramine were not unexpected because these drugs are receptor selective rather the receptor specific (12).…”
Section: Accepted Manuscriptmentioning
confidence: 99%